The Knowledge related to Mental Health of the People around the Coastal Areas - Taty Hernawaty; Hadi Suprapto Arifin; Efri Widianti (Jurnal Keperawatan Indonesia, 2020)
Mental health is one of Indonesia’s public health development goals. The Pangandaran District Administration of West Java is an expanded district that actively carries out various development programs, including mental health programs. This study aimed to identify public knowledge about mental health in Pangandaran District using quantitative descriptive method. The research population comprised residents of the Pangandaran District, and a sample was collected via cluster multistage sampling technique. The sample was gradually determined in the order of subdistricts, villages, subvillages, community units, and neighborhood units. The total sample was composed of 113 respondents. The questionnaire was developed based on theories and concepts on public mental health and distributed to participants after validity and reliability tests were conducted. The construct validity test result was between 0.303 and 0.764, which meant that all items were valid. The Kuder-Richardson 20 formula was used to test reliability, and the reliability coefficient was 0.887. Mathematical calculations were used for data analysis; data are presented as frequency distributions. In this study, 61.10% of the respondents had “less” knowledge, 33.59% had “good” knowledge, and the remaining 5.30% had “enough” knowledge of mental health. The results suggest that the local government should provide mental health education for the residents. For educational institutions, mental health programs should be a fundamental offering in Indonesian society. Abstrak Pengetahuan tentang Kesehatan Mental Warga di Sekitar Wilayah Pesisir. Sehat secara mental merupakan bagian dari tujuan pembangunan kesehatan masyarakat. Pemerintah Kabupaten Pangandaran merupakan kabupaten pemekaran yang sedang menggalakkan berbagai program pembangunan termasuk program kesehatan jiwa. Penelitian ini bertujuan mengidentifikasi pengetahuan masyarakat Kabupaten Pangandaran mengenai kesehatan jiwa. Metode penelitian menggunakan deskriptif kuantitatif. Populasi penelitian adalah seluruh masyarakat Kabupaten Pangandaran dan sampel diambil menggunakan tehnik cluster multistage sampling. Tahapan penetapan sampel dilakukan bertahap mulai dari kecamatan, desa, dusun, rukun warga, sampai rukun tetangga dan didapat sebanyak 113 orang. Data penelitian dikumpulkan melalui kuesioner dan dibagikan pada seluruh responden. Kuisioner dikembangkan dari teori dan konsep kesehatan jiwa masyarakat dan sudah dilakukan uji validitas dan reliabilitas. Uji validitas konstrak didapatkan hasil berkisar antara 0,303 sampai 0,764 sehingga semua item dinyatakan valid. Uji reliabilitas menggunakan uji Kuder Richardson 20 dan diperoleh koefisien reliabilitas KR-20 sebesar 0,887. Analisa data menggunakan perhitungan matematis dan ditampilkan dalam bentuk tabel distribusi frekuensi. Hasil penelitian menunjukkan bahwa 61,10% responden kurang memiliki pengetahuan mengenai kesehatan jiwa, 33,59% responden memiliki pengetahuan mengenai kesehatan jiwa yang baik, dan sisanya 5,30% responden memiliki pengetahuan mengenai kesehatan jiwa yang cukup. Saran, bagi pemerintah setempat agar memberikan pendidikan kesehatan jiwa bagi masyarakat. Bagi instansi pendidikan, diharapkan menjadi data dasar dalam membuat program kesehatan jiwa di masyarakat. Kata Kunci: Jawa Barat, kesehatan masyarakat, program kesehatan jiwa, wilayah pesisir